Perkembangan Moral Anak Usia Sekolah Dasar: Studi Kualitatif Berdasarkan Observasi di Lingkungan Sekolah - Karmila Karmila; Fadillah Syukri; Nadya Salsabila; Ari Suriani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to describe the moral development of elementary school-aged children through a qualitative approach based on observation. Two fifth-grade students were observed to identify differences in moral characteristics and the influence of social interaction on the formation of moral values. The study also examines the teacher’s role as a facilitator of moral growth, support strategies for students with difficulties, the relationship between moral development and cognitive ability, and the role of parents. Findings reveal that children's moral development is significantly influenced by contextual, relational, and reflective learning approaches. Personalized support from teachers and collaboration with parents positively contribute to students’ moral maturity. The study recommends integrating moral values into the curriculum, training for teachers, and strengthening school–family cooperation.